Perilaku Kepemimpinan dan Motivasi Kerja dalam Meningkatkan Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Perusahaan Pembiayaan di Kota Jambi - Dimas Iskandar; Singmin Johanes Lo (Universitas Batanghari, 2022)
The purpose of this study was to analyze leadership behavior and work motivation in improving employee performance with job satisfaction as an intervening variable at a financing company in the city of Jambi, the subject in this study was employees who worked at a financing company in Jambi City, with a sample of 230 people. The research used is structural equation modeling. The results show that leadership behavior and work motivation will have more impact on employee performance if mediated by job satisfaction at a finance company in the city of Jambi.